Comparative Analysis of Different Control Strategies for Relift Luo Converter - R. Banupriya; R. Nagarajan; K. R. N. Kalis (International Journal of Photoenergy)
Dual-output DC to DC converters have drawn attention in the domestic, automobile, and industrial domains. A dual-output converter usually provides a voltage step-down channel and a voltage step-up channel. Typically, an automobile needs a battery charging unit, a traction motor drive, and several other applications. A typical application may require two channels of DC output with a low-voltage (LV) channel and a high-voltage (HV) channel. While the generic boost-derived and quadratic boost-derived dual-output converters are available in the literature, this article focuses on the control aspects of a relift type Luo converter-derived dual-output converter (LDDOC). A solar photovoltaic (SPV) source is the main power, and it charges a battery. The LV loads may be connected across the battery, and the relift stage delivers a regulated 48 V output. The regulation of the 48 V output using a PI controller, a fuzzy logic controller, an ANN-based controller, and a sliding mode controller (SMC) has been studied using simulations. The simulations reveal that the sliding mode controller is advantageous because of meeting out the required performance, easy implementation, and low cost. An experimental setup has also been developed to verify the performance of the sliding mode controller for the regulation of the HV channel output voltage at 48 V.